Insulinoma – how to localize the tumor? - Kiković, Saša; Tavčar, Ivan; Dragović, Tamara; Ristić, Petar; Karajović, Jelena; Marinković, Dejan; Perišić, Nenad; Rusović, Siniša; Hajduković, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Arterial stimulation with calcium and venous sampling (ASVS) enables us to reach the goal of avoiding that any patient with insulinoma undergoes a blind surgical exploration. Since ASVS is both a functional and morphological localization procedure, its sensitivity is not influenced by factors that are causing the insensitivity of usual anatomical and morphological procedures. Based on our own experience in preoperative localization of insulinoma, we indented to show why we believe that ASVS should be performed to all patients regardless of data collected from other preoperative localization methods. Methods. We have analyzed the accuracy of preoperative localization methods retrospectively. First anatomical and morphological procedures like transabdominal ultrasound (US), endoscopic ultrasound (EUS), computed tomography (CT) and magnetic resonance imaging (MRI) were done. Then we analyzed the data collected during a functional procedure which, at the same time, allows regionalization (ASVS). To estimate the accuracy, the results of every single method were correlated with the operative findings in all sixteen cases. Results. Prior to ASVS, fourteen patients underwent US, fifteen had CT, MRI was performed in eight patients and EUS in thirteen. Using only one of these methods enabled identification of tumors in five patients, using two methods in six patients while three and four in one patient each. For three patients, none of these methods was successful. ASVS revealed that all seen tumors were functional except three of the six visualized with two methods (US and EUS). In two of these three cases, US and EUS localized the tumors in pancreatic tail/body while ASVS accurately identified the tumors in pancreatic head. For these patients US and EUS showed false positive results. In the third of these patients EUS showed the tumor localized in pancreatic head, while US and ASVS accurately pointed to tail. This, too, was a false positive result of EUS. ASVS successfully provided regionalization data in three patients where other visualization methods failed. Operative and later histological findings confirmed the accuracy of ASVS in all sixteen patients including two patients that previously underwent distal pancreatectomy based on false positive EUS findings. Conclusion. Two patients, with accurate insulinoma regionalization in pancreatic head, obtained with ASVS, previously underwent unsuccessful distal pancreatectomy based on the false positive EUS findings. The same goes to three other patients with the false positive results obtained with other anatomical and morphological findings, as well as those three patients that had no preoperative visualization with other methods prior to ASVS. Therefore we suggest ASVS performing in each suspected insulinoma patient before the surgery, regardless of the data collected using other methods. This would enable us to test functional characteristics of visualized findings and to regionalize part of pancreas with uncontrolled insulin secretion when no suspicious changes were found.
Keywords: insulinoma; diagnosis; calcium gluconate; injections, intra-arterial; sensitivity and specificity.